SPA & Wellness Center Design - Lestina Novyta Purba; Husna Izzati; Fajar Ikhwan Harnomo (Jurnal Arsitektur Archicentre, 2022)
Currently, it is a necessity and a trend in health therapy to pamper oneself for modern society. The increasing need for health facilities (wellness) and spa relaxation in today's environment is proof of the high interest in lifestyle in modern society. The design of the Spa & Wellness Center is present as a place that accommodates various facilities in the form of relaxation activities, and a complete health and fitness clinic. Supporting the tourism sector according to government programs in health tourism/wellness tourism is very useful to adjust to the needs of modern society in the city of Bandung. The method used in this design is an architectural design method with an Organic Architecture approach. The results obtained from the Organic Architecture approach are applied to lighting systems, ventilation and land contours such as determining the position of openings, materials, mass forms, and controlling the lighting that will be obtained by each building. The design variables that will be the topic of discussion include contour land, the shape of the mass material, the use of materials, and the facilities contained in the building. From the results of this design obtained a commercial building that has the function of health (wellness) and spa relaxation is expected to be a building that is considered good not only in the function of the building but in its aesthetics and form.